2020
DOI: 10.2196/15806
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone-Based Health Care Chatbot to Promote Self-Management of Chronic Pain (SELMA): Pilot Randomized Controlled Trial

Abstract: Background Ongoing pain is one of the most common diseases and has major physical, psychological, social, and economic impacts. A mobile health intervention utilizing a fully automated text-based health care chatbot (TBHC) may offer an innovative way not only to deliver coping strategies and psychoeducation for pain management but also to build a working alliance between a participant and the TBHC. Objective The objectives of this study are twofold: (1)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(179 citation statements)
references
References 98 publications
7
153
2
Order By: Relevance
“…mHealth interventions probably allow more frequent, higher quality, and more cost-effective contacts compared with conventional behavior change interventions (eg, face-to-face or telephone-based interventions). With the advancement of smart technology, nonhuman conversational agents powered by artificial intelligence (eg, Chatbot) can also play the role of e-coaching and connect with e-contacts to promote people’s health [ 74 ]. Further studies should examine the components (eg, social support, contact) that are more effective in yielding clinical benefits and those components should be strengthened to achieve these benefits.…”
Section: Discussionmentioning
confidence: 99%
“…mHealth interventions probably allow more frequent, higher quality, and more cost-effective contacts compared with conventional behavior change interventions (eg, face-to-face or telephone-based interventions). With the advancement of smart technology, nonhuman conversational agents powered by artificial intelligence (eg, Chatbot) can also play the role of e-coaching and connect with e-contacts to promote people’s health [ 74 ]. Further studies should examine the components (eg, social support, contact) that are more effective in yielding clinical benefits and those components should be strengthened to achieve these benefits.…”
Section: Discussionmentioning
confidence: 99%
“…23 Results from a pilot trial of an AI-chat bot to promote selfmanagement of chronic pain (SELMA) were recently published with encouraging results. 24 Many of these chat bots function as promising forms of asynchronous telehealth for advice to out of hospital patients. This helps to filter patients that primarily require reassurance or advice, from those who may need further synchronous video consultations or in-person review.…”
Section: Conversational Artificial Intelligencementioning
confidence: 99%
“… 23 Results from a pilot trial of an AI-chat bot to promote self-management of chronic pain (SELMA) were recently published with encouraging results. 24 …”
Section: Conversational Artificial Intelligencementioning
confidence: 99%
“…CAs are software programs that imitate natural interactions with human users by engaging in a human-like text-based and/or voice-enabled dialog [ 24 , 25 ]. Recent research has shown the ability of CAs to positively affect patient satisfaction [ 26 ], therapeutic alliance [ 27 , 28 ], and health-related outcomes [ 29 , 30 ]. Moreover, an overall acceptability has been established in various populations [ 31 ].…”
Section: Introductionmentioning
confidence: 99%